Peningkatan Prestasi Belajar Seni Rupa Materi Origami Melalui Model PjBL Berbantuan Media Papan Pola Alur - Rah Hajeng Listiawati; Okto Wijayanti (CV. Global Cendekia Inti, 2026)
The low academic achievement of students in visual arts serves as the practical problem underlying this research. Specifically in folding, cutting, and pasting skills in terms of both conceptual understanding and practical ability. The study aimed to examine the implementation of the Project-Based Learning (PjBL) model supported by